The effect of internal capabilities and external environment on small- and medium-sized enterprises' international performance and the case of the Malaysian halal food industry - Ismail, Noor Azlin; Kuivalainen, Olli (Springer, 2015)
This study investigates the internal capabilities, the external environment, and the moderating effect of geographical scope (international or global geographical presence) on the international performance of small- and medium-sized enterprises in the Malaysian halal food industry. Although the majority of research on SME internationalization concerns developed countries and knowledge-intensive industries, this study focuses on an emerging global industry from the perspective of a developing country. Furthermore, most of the literature on international entrepreneurship neglects the role of geographical scope as a moderator: current findings are still inconclusive with regard to the factors that affect performance on various levels of foreign market presence. The findings of our holistic study, in which we use several complementary theories as a backdrop, reveal the need to investigate internal and external factors in parallel with geographical scope to enhance understanding of their effect on the international performance of SMEs.